2009
DOI: 10.1029/2008jb005814
|View full text |Cite
|
Sign up to set email alerts
|

Structural features and shear‐velocity structure of the “Pacific Anomaly”

Abstract: 1] We constrain structural features and shear-velocity structure of a low-velocity anomaly in the lower mantle beneath the Pacific (we term it the ''Pacific Anomaly'') on the basis of forward travel time and waveform modeling of the observed direct S, Sdiff, ScS, SKS, and SKKS phases sampling a great arc across the anomaly from eastern Eurasia to southern South America. After correction for the effects of earthquake mislocation and the seismic heterogeneities outside the Pacific Anomaly, seismic observations s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(107 citation statements)
references
References 47 publications
6
101
0
Order By: Relevance
“…Using a material with higher bulk modulus than ambient mantle is crucial in generating stable, steep-edged, high-elevation chemical structures [Tan and Gurnis, 2007]. Seismic waveform studies have found steep edges in several parts of LLSVPs [Ni et al, 2002;To et al, 2005;Wang and Wen, 2007;He and Wen, 2009]. The high elevation of LLSVPs suggests that they are nearly neutrally buoyant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a material with higher bulk modulus than ambient mantle is crucial in generating stable, steep-edged, high-elevation chemical structures [Tan and Gurnis, 2007]. Seismic waveform studies have found steep edges in several parts of LLSVPs [Ni et al, 2002;To et al, 2005;Wang and Wen, 2007;He and Wen, 2009]. The high elevation of LLSVPs suggests that they are nearly neutrally buoyant.…”
Section: Discussionmentioning
confidence: 99%
“…LLSVPs cover about 20% of the core-mantle boundary (CMB) by area [Burke et al, 2008] and have high elevation, extending at least 500 km above the CMB [Ni et al, 2002;He and Wen, 2009]. The shear wave velocity anomaly and bulk sound velocity anomaly of the LLSVPs are anticorrelated [Masters et al, 2000;Ishii and Tromp, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…The two LLSVPs are located nearly antipodal beneath Africa and the central Pacific Ocean, both with high elevations and steep side boundaries based on seismic waveform modeling studies (Ni et al, 2002;Ni and Helmberger, 2003;He and Wen, 2009). The African one extends 1200-1500 km upward from the core-mantle boundary (CMB) with steep and sharp side boundaries (Ni et al, 2002;Wang and Wen, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Using the waveforms and traveltimes of a suite of shear wave phases sampling the lowermost mantle, He & Wen (2009) infer that the West Pacific anomaly reaches 740 km above the CMB and has steep sides. In He & Wen (2012), they confirm the presence of a separate anomaly to the east, 450 km high and bounded by shallowly sloped sides.…”
Section: Comparison With Regional Seismic Studiesmentioning
confidence: 99%